The Green Freighter Project – Objectives and First Results - Kolja Seeckt and Wolfgang Heinze and Dieter Scholz (Optimage Ltd., 2008)
This paper introduces the Green Freighter project – a joint aircraft design research project with focus on the design and investigation of environmentally friendly and cost effective freighter aircraft. The project partners are the Hamburg University of Applied Sciences (HAW), the Institute of Aircraft Design and Lightweight Structures (IFL) of the Technische Universität Braunschweig, Airbus’ Future Projects Office and Bishop GmbH. During the project, unconventional configurations – first and foremost the blended wing body (BWB) – and the use of alternative fuels will be investigated in comparison to conventional kerosenepowered aircraft. As a first step, theoretical jet versions of the regional aircraft ATR 72 were re-designed and investigated. The preliminary sizing of an initial kerosene version was done using the HAW’s Preliminary Sizing Tool (PreSTo) assuming a completely new design. In comparison, two jet-powered derivatives of the real aircraft were set up and investigated as both a kerosene- and a hydrogen-powered version using the IFL’s Preliminary Aircraft Design and Optimization program (PrADO). The results show that for a conversion from kerosene to liquid hydrogen as fuel a lot of cargo volume has to be sacrificed for internal tank volume if external tanks shall be avoided. Assuming today’s fuel prices, the direct operating costs (DOC) of the hydrogen version are significantly higher. In the future, however, with changing availability and prices for different fuels, the numbers are expected to change significantly and make the hydrogen version more favorable.
Keywords: aircraft design; freighter; hydrogen; propulsion system; conversion